2022
DOI: 10.1186/s12871-022-01595-8
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of different concentrations of ropivacaine in transversalis fascia plane block during laparotomy

Abstract: Objective To explore the analgesic effects of different concentrations of ropivacaine in transversalis fascia plane (TFP) block during laparotomy. Methods Ninety patients who underwent laparotomy admitted to our hospital from March 2019 to March 2020 were selected as the study subjects and were divided equally into a low concentration group, a medium concentration group, and a high concentration group according to the randomized grouping method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Lee et al [ 12 ] also compared low-concentration ropivacaine and high-concentration ropivacaine in transverse abdominis plain blocks in pediatric open inguinal hernia repair. Han et al [ 13 ] and Tian et al [ 14 ] reported the analgesic effects of different ropivacaine concentrations in patients undergoing hip replacement and laparotomy. Previous studies reported that 0.75% ropivacaine was within the safety limits.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 12 ] also compared low-concentration ropivacaine and high-concentration ropivacaine in transverse abdominis plain blocks in pediatric open inguinal hernia repair. Han et al [ 13 ] and Tian et al [ 14 ] reported the analgesic effects of different ropivacaine concentrations in patients undergoing hip replacement and laparotomy. Previous studies reported that 0.75% ropivacaine was within the safety limits.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have pointed out that low-concentration ropivacaine will not cause complete blockade of nerves because it will not significantly affect the patient's respiratory function, which improves the safety of treatment [ 15 ]. Tian et al [ 16 ] used 0.4%, 0.5%, and 0.6% of ropivacaine for anesthesia, and found that the total adverse reaction rate of 0.6% ropivacaine was significantly higher than that of the low-concentration group. The results are consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Currently, ropivacaine is the most commonly used local anaesthetic for PNB due to its lower toxicity in the central nervous system and heart. 7 8 The concentrations of ropivacaine used for PNB are various, and the efficacy and safety of different concentrations of ropivacaine have been compared in several RCTs, [9][10][11][12][13][14] but the results were inconsistent. Therefore, it is meaningful to perform a systematic review and meta-analysis to determine the optimal concentration of ropivacaine for PNB, which may provide longer analgesia without increasing the incidence of adverse effects.…”
Section: Introductionmentioning
confidence: 99%